IMPLEMENTASI PLATFORM KHAN ACADEMY PADA PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN HYBRID DI SEKOLAH INDONESIA KUALA LUMPUR (SIKL) - Aziza, Ayu; Winarti, Puji; Sarwono, Ridha; Sri Legowo , Yogi Ageng (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Mathematics is an important foundation in human intellectual development and daily life, yet many students struggle to understand its abstract concepts. This study aims to explore the effectiveness of Khan Academy-based hybrid learning in improving students’ understanding and engagement in SIKL. The research subjects were 9 students in grades 3-5 (aged 9-14 years). The method used was mixed, with quantitative data through pre-test and post-test on basic mathematical concepts on Geometry and fraction, analyzed using paired t test, as well as qualitative data from questionnaires and content analysis. The study was conducted over 28 days with a hybrid approach combining online learning with Khan Academy and offline guiding by tutor assistance. Statistical analysis using the paired t test showed a significant increase between pre-test and post-test scores (p = 0.0074), with an average difference of 17.33. This finding indicates an increase in students' understanding of basic math concepts. Qualitative analysis showed that 88.89% of students found hybrid learning interesting, 77.78% found the material easier to understand, and 33.33% appreciated the combination of online and offline learning. However, students also suggested improvements in video quality (44.44%) and learning duration (33.33%) This study concluded that the Khan Academy-based hybrid approach is effective in improving students' mathematical understanding. However, the success of this approach still requires the role of tutors in explaining concepts that are difficult to understand.With improvements in video quality and lesson duration settings, this approach has the potential to be applied more widely.